Comparison of Giving Mecobalamin Supplements to Improve the Severity of Painful Diabetic Neuropathy - Irsyadat, Andi Muhammad; Aulina, Susi; Goysal, Yudy; Zainuddin, Andi Alfian; Lotisna, Mimi; Amran, Muhammad Yunus (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Diabetic Painful Neuropathy (DPN) is caused by the progressive loss of nerve fibers due to hyperglycemia, oxidative stress, andhomocysteinemia. Mecobalamin supplementation has shown potential in improving peripheral neuropathy symptoms by enhancing nerve conduction and alleviating neuropathic pain. However, its efficacy data remains limited. This research to investigated the effect of mecobalamin supplementation on the severity of Painful Diabetic Neuropathy in type 2 diabetes mellitus patients. This research is a non-randomized clinical trial, 16 patients were given 500 ?g of intramuscular Mecobalamin 8 times over 30 days (n=8) and 5 times over 10 days (n=8). Subjects underwent measurements VAS, TSS, BDNC and ENMG before and after intervention. VAS (p-value=0,022), TSS (p-value=0,020) and BDC (p-value=0,003) was significant improved in 8 times administration group. VAS (p-value=0,045) dan BDC (p-value=0,014) was significant improved in 5 times administration group, where TSS improved but not significant. The 8 times administration group was better compared to the 5 times administration group in improvement of VAS (p-value=0,016). Based on this research, The addition of mecobalamin 8 times and over 5 times in the management of Diabetic Neuropathic Pain can be useful in reducing neuropathic pain.